1982
DOI: 10.1136/ard.41.1.15
|View full text |Cite
|
Sign up to set email alerts
|

A sequential study of the relationship between faecal Klebsiella aerogenes and the common clinical manifestations of ankylosing spondylitis.

Abstract: SUMMARY An 8-month sequential study at 4-weekly intervals of faecal Klebsiella aerogenes and clinical activity of ankylosing spondylitis is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Ebringer et al (1 977) found that faecal carriage of klebsiellas in patients with AS was associated with active disease, but other workers could not confirm this observation (Eastmond, Cooke and Wright, 1978;Warren and Brewerton, 1979a). However, Ebringer, Cawdell and Ebringer (1979) and Eastmond et al (1980) showed an association between klebsiella carriage and anterio uveitis but this was not supported by the findings of Warren and Brewerton (1 9 7 9 4 and sequential studies of klebsiella carriage have also produced conflicting results Warren and Brewerton, 1980;Eastmond et al, 1981).…”
Section: Introductioncontrasting
confidence: 48%
“…Ebringer et al (1 977) found that faecal carriage of klebsiellas in patients with AS was associated with active disease, but other workers could not confirm this observation (Eastmond, Cooke and Wright, 1978;Warren and Brewerton, 1979a). However, Ebringer, Cawdell and Ebringer (1979) and Eastmond et al (1980) showed an association between klebsiella carriage and anterio uveitis but this was not supported by the findings of Warren and Brewerton (1 9 7 9 4 and sequential studies of klebsiella carriage have also produced conflicting results Warren and Brewerton, 1980;Eastmond et al, 1981).…”
Section: Introductioncontrasting
confidence: 48%
“…It is known that changes in the gut flora in humans may be associated with the development of reactive arthritides as shown by postdysenteric Reiter's syndrome, and it has also been reported that there is an increased faecal carriage rate of certain Klebisella species that correlates with disease activity in patients with ankylosing spondylitis.25 26 Patients with coeliac disease develop antibodies to many dietary constituents, but the relevance of these antibodies and of circulating immune complexes to the pathogenesis of lesions in and outside the gastrointestinal tract is unknown. Only occasional reports of coeliac disease and rheumatoid arthritis occurring in the same patient have appeared.6 21 Our 3 patients all from the same unit would suggest that perhaps this association is more frequent than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the association of HLA-B27 with other forms of so-called reactive arthritides or seronegative spondylarthritides (Moll et al 1974), a number of authors (Calin et al 1977, Gerber et al 1977, Esdaile et al 1977) denied any diagnostic value of HLA-typing, whereas others (Golding & Jenkins 1974, Hill et al 1976, Tausch et al 1977, Eastmond et al 1980 concluded that HLA-B27 determinations may be of diagnostic importance in the classification of oligoathritides and particularly in the often atypical forms of female AS. There is general agreement now that HLA-typing has no value in definite AS as defined by the New York Criteria.…”
Section: Hla-b27 Determination As a Diagnostic Toolmentioning
confidence: 99%